VD_FINDINFO Ord / 2010 / 7 vom 25. Mai 2010 - VD Tribunal cantonal (2010)
COTISATION AVS/AI/APG, ACTIVITÉ LUCRATIVE INDÉPENDANTE, MESURE PROVISIONNELLE, SUSPENSION DE LA PROCÉDURE | 25 LPA-VD, 86 LPA-VD, 94 al. 2 LPA-VD